In Vitro Antibiofilm Activity of Ethyl Acetate Fraction of Coriander Seeds (Coriandrum sativum) Against Enterococcus faecalis ATCC 29212 - Akbar Dwipasya Haliyudha Warokka; Asikin Nur; Indah Titien Soeprihati (Odonto : Dental Journal, 2026)
Background: Enterococcus faecalis is frequently associated with persistent root canal infections due to its ability to form resistant biofilms. However, evidence regarding the antibiofilm activity of specific plant-derived fractions, particularly the ethyl acetate fraction of coriander seeds (Coriandrum sativum), remains limited. This study aimed to evaluate the effect of different concentrations of this fraction on E. faecalis ATCC 29212 biofilm formation.Method: Dried coriander seeds were extracted using ethanol and subsequently fractionated with ethyl acetate to obtain the active fraction. Biofilm inhibition was assessed using a 96-well polystyrene microplate assay after exposure to various concentrations. Calcium hydroxide was used as a control. Biofilm biomass was quantified by measuring optical density (OD). Each group was tested in five replicates (n=5). Statistical analysis was performed using one-way ANOVA followed by a Bonferroni post-hoc test.Result: All tested materials exhibited inhibitory activity against E. faecalis biofilms. Calcium hydroxide showed the highest mean inhibition (69.41%), while the 16% concentration of coriander seed ethyl acetate fraction demonstrated the strongest activity among the experimental groups (64.89%). Statistical analysis revealed significant differences between concentration groups (p < 0.05).Conclusion: The ethyl acetate fraction of coriander seeds demonstrated concentration-dependent antibiofilm activity against E. faecalis ATCC 29212 in vitro. Higher concentrations showed greater inhibitory effects, however, further studies are required to confirm its clinical applicability.